Sketch Out the Myth of Wisdom and Blessing of Islamic Boarding School - Zainuddin Syarif; Abdul Gaffar (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
Boarding school culture is a part of Islamic social setting that acknowledges the differences of human "faith" in an intellectual approach to the problem that has been revealed in the empirical world. Boarding school tradition is one of the cultural acculturation forms of Islamic studies. There is a reflection that the â€œsantriâ€ relation to the "kiai" is an obedience of â€œsam'an wa ta'atanâ€ by hoping to bless in order that they can get better lives. The blessing is part of the justification of religious symbol that is given by â€œsantriâ€ to their "kiai" such as blessing, â€œkaramahâ€ that function as the power source. Santri' assumptions to the "kiai" have the practice of "hisb" that is believed can result in blessing and clairvoyant. Those symbolic terms are like Barakah (blessing), tawadu', muru'ah, and other irreplaceable symbols that have negative meanings for santri like afraid to be cursed. Good attitudes of kiai always show and utilize symbols that contain moral discipline values (religion) to internalize in building a cultural formula of the blessing myths.